Holding the note : profiles in popular music - Remnick, David (Alfred A. Knopf, 2023)
"The greatest popular songs, whether it's Aretha Franklin singing "Respect" or Bob Dylan performing "Blind Willie McTell," have a way of embedding themselves in our memories. You remember a time and a place and a feeling when you hear that song again. In Holding the Note, David Remnick writes about the lives and work of some of the greatest musicians, songwriters, and performers of the past fifty years"--